STATE AND IMMIGRATION: TRANSNATIONAL ORGANIZATIONS AND LOCAL DEVELOPMENT IN SINALOA, MEXICO - Pintor Sandoval, Renato (2019)
This article analyzes the behavior of Sinaloa’s migrant clubs and their social and economic impact in their places of origin. Firstly, the actions of the San José Club are analyzed, which, supported by the Sinaloan Fraternity in California, makes it possible to have a social impact in a transnational manner through practices and community links. Secondly, the Elotense Fraternity in California is analyzed, which under the initiatives of the municipal presidents in turn and under the scheme of the 3x1 program, allow  the development of local infrastructure investments in favor of the locality of origin, surpassing the group of organized migrants´ founding principle,  which is to keep community activities alive transnationally.